Removal of sulfamethizole from aqueous solution using advanced oxidation processes effects of pH and salinity - Wang, A M (Water science and technology : a journal of the International Association on Water Pollution Research, 2020)
This study investigates the removal of sulfamethizole (SFZ) in ozone (O3), O3/Na2S2O8 (sodium persulfate), UV/Na2S2O8, UV/O3, and UV/O3/Na2S2O8 systems. The effects of pH and salinity on SFZ mineralization were evaluated. The mineralization of SFZ followed pseudo-first-order kinetics. At pH 5, the rate constants of SFZ mineralization in O3, O3/Na2S2O8, UV/Na2S2O8, UV/O3, and UV/O3/Na2S2O8 systems were 0.576, 0.924, 0.702, 1.26, and 5.21 h-1, respectively. The SFZ mineralization rate followed the order pH 5 > pH 7 > pH 9 in all tested advanced oxidation processes. Salinity increased the rate of SFZ mineralization in O3 and O3/Na2S2O8 systems and decelerated it in UV/Na2S2O8, UV/O3, and UV/O3/Na2S2O8 systems. UV/O3/Na2S2O8 was the best system for mineralizing SFZ, and sulfate radicals were the predominant species in UV/O3/Na2S2O8